624 IFNγ secreted by tebentafusp (IMCgp100)-redirected T cells inhibits expression of melanin synthesis pathway genes in healthy melanocytes. (9th November 2020) - Vardeu, Mariantonella; Depoil, David; Britton-Rivet, Camille; Houghton, Jane; Harper, Jane; Provost, Gabrielle Le; Collins, Laura; Ranade, Koustubh; Benlahrech, Adel
Abstract : Background: Tebentafusp (IMCgp100) is a bispecific T cell redirector comprised of an affinity-enhanced TCR recognising melanocyte lineage antigen gp100 and a T cell engaging anti-CD3 scFv domain. Tebentafusp has shown activity as monotherapy in advanced cutaneous and uveal melanoma (Middleton et al ., ASCO 2019), and we have previously reported that over half of uveal melanoma patients treated with tebentafusp display melanocyte-related adverse events (MRAE). These include vitiligo/skin hypopigmentation, leukotrichia, and hyperpigmentation and, collectively, are associated with better overall survival in uveal patients receiving tebentafusp (Orloff et al, AACR 2020). In this study, we dissected the mechanisms by which tebentafusp may induce MRAE and highlight the potential clinical significance. Methods: In vitro studies were conducted to assess the direct and indirect effects of tebentafusp on epidermal melanocytes from healthy donors. Expression of gp100 and the gp100:HLA*02:01 target complex by melanocytes were quantified at the mRNA level and on the cell surface by confocal microscopy, respectively. Melanocytes co-cultured with PBMC and increasing concentrations of tebentafusp were assessed for their susceptibility to lysis and/or ability to stimulate cytokine production. These readouts were compared to gp100-positive and negative melanoma cancer cell lines. Melanin production by melanocytes was quantified and the melanin synthesis pathway interrogated at the mRNA and protein level following exposure to secretomes from tebentafusp-redirected PBMC against melanoma cancer cells. Results: Healthy melanocytes expressed 2 to 3-fold lower levels of gp100 peptide-HLA complexes on their surface compared to gp100-positive melanoma cell lines. In the presence of tebentafusp, this lower target expression translated into 3–6 fold lower levels of IFNγ and more than 100 fold lower granzyme B production by redirected T cells and these melanocytes were resistant to direct tebentafusp-induced killing (EC50 for melanocytes greater than 1nM vs EC50 melanoma cell lines of 23–50 pM). Supernatants from T cells activated in response to melanoma cancer cells by tebentafusp downregulated the melanin content of healthy melanocytes (20–30% reduction). Western blotting revealed 30–40% inhibition of two key components of the melanin synthesis pathway; the tyrosinase-related protein (TRP)-1 and TRP-2. This inhibition was reversed by blocking IFNγ in supernatants from activated T cells. Conclusions: MRAEs, especially vitiligo, associated with response to tebentafusp, may be explained, at least in part, by the downregulation of melanin biosynthesis pathway genes by IFNγ secreted by tebentafusp-activated T cells. Ethics Approval: The study was approved by the South Central - Oxford A Research Ethics Committee (UK), REC reference 13/SC/0226 References: Middleton, et al., Relationship between clinical efficacy and AEs of IMCgp100, a novel bispecific TCR–anti-CD3, in patients with advanced melanoma. Journal of Clinical Oncology . 2019. Orloff, et al., Vitiligo and other clinical melanocyte-related adverse events following tebentafusp (IMCgp100) exposure in patients with uveal melanoma. AACR (American Association for Cancer Research), 2020.